Can Experiental Marketing, Product Innovation and Brand Image Be the Solution for Consumer Purchase Decisions at A&W Restaurant: Case Study in Carrefour Serang - Hayati Nupus; Jamjuri (CV ODIS, 2022)
This study aims to analyze the effect of experiential marketing, product innovation and brand image on consumer purchasing decisions on A&W products. The research method uses a quantitative with a causal design and a survey approach conducted on A&W consumers at Carrefour Serang. The number of samples taken is 6 x 16 indicators, namely 96 respondents. This study specifically proves that experiential marketing has a significant positive effect on purchasing decisions, product innovation has a significant positive effect on purchasing decisions and brand image has a significant positive effect on purchasing decisions. The adjusted R Square value of 0.803 indicates that experiential marketing, product innovation and brand image have the ability of 80.3% (0.803 x 100%) in explaining variations in purchasing decisions. The remaining 19.7% variation in purchasing decisions is explained by other variables not examined in this study. It can be seen that experiential marketing is the independent variable that has the greatest influence on the purchasing decisions of A&W customers at Carrefour Serang.